CAR-T cell therapy in relapsed or refractory multiple myeloma and access in Turkey - Hakan, Goker; Engin, Kelkitli; Elifcan, Karakulak Aladag; Haluk, Demiroglu; Mehmet, Turgut; Suman, Kambhampati; Maxwell, Krem (Frontiers in Medicine, 2024)
The past decade has seen the development of immunotherapy for the treatment of multiple myeloma (MM), beginning with monoclonal antibodies (mAbs) in the relapsed and refractory setting and culminating in the market approval of chimeric antigen receptor T cells (CAR-T) and bispecific antibodies (BsAbs). The medical community is evaluating the efficacy and safety of these targeted immunotherapies, most of which currently target B-cell maturation antigen (BCMA) on the surface of plasma cells. Two anti-BCMA CAR-T products are available for treating relapsed or refractory MM: idecabtagene vicleucel (ide-cel) and ciltacabtagene autoleucel (cilta-cel). Ide-cel and cilta-cel demonstrate the ability to induce deep responses in heavily pretreated diseases, including patients with triple-class-refractory and penta-refractory diseases. However, there are key similarities and differences regarding these agents, unknowns regarding their comparative efficacy and toxicity, and mechanisms underlying resistance to these new immunotherapies. This review discusses CAR-T cell therapy in relapsed refractory MM, with focus on efficacy, toxicities and the evolving trajectories of these therapies in the USA, as well as access in Turkey.Multiple myeloma (MM) is a neoplasm that is qualified with clonal proliferation of malignant plasma cells in the bone marrow and/or extramedullary tissues. It accounts for approximately 15% of hematologic malignancies (1). MM treatment has made great strides over the past several decades, however, despite substantial. Advances multiple myeloma (MM) remains a largely incurable disease which underscores the unmet need for more effective treatment approaches. In recent years, T cell redTrectTon therapTes for relapsTng/refractory MM ( RRMM), especTally chTmerTc antTgen receptor T cells (CAR-T) and bTspecTfTc antTbodTes (BsAbs), have been significant advances. Chimeric antigen receptor (CAR) T cell therapy involves the modification of patient or donor T cells to target specific cell surface antigens (2, 3) and our review will focus on the two approved products in the USA. Since 2021, CAR-T has emerged as a promising immunotherapy for RRMM. Currently approved products are autologous, where T cells obtained from patients are genetically manipulated to a specific tumor-targeted receptor called the chimeric antigen receptor (CAR). (4)